Market neutral volatility: a different approach to the S&P 500 options market efficiency - Ruas, João Pedro Bento (2011)
Under the efficient market hypothesis, an options price’s implied volatility should be the best possible forecast of the future realized volatility of the underlying asset. In spite of this theoretical proposition, a vast number of studies in the financial literature found that implied volatility is a biased estimator of the future realized volatility. These findings suggest that we are either in the presence of an inefficient market or that econometric models fail on that purpose. In this thesis, by introducing the concept of Market Neutral Volatility and the derivation of a theoretical model, we show what in fact the implied volatility forecasts and we prove that the S&P 500 options market is efficient. This property of the S&P 500 options market assures that the implied volatility cannot be a biased forecast of its future realized volatility. Thus, we conclude that the bias of the implied volatility estimator is due to the inadequacy of the commonly used econometric approaches.